2016
DOI: 10.17795/ijcp-7229
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Monitoring of Occupational Exposure to Cyclophosphamide Drug in Two Iranian Hospitals

Abstract: Background: Most cytotoxic drugs are unable to discriminate normal cells from cancer cells and they interfere with cell division and could lead to harmful effects such as carcinogenicity, genetic mutation, and teratogenicity. In order to assess dermal occupational exposure to cytotoxic drugs, surface sampling was used to determine the residual drugs on the working surfaces, as well as the effectiveness of the procedures for cleaning the treatment area. Objectives: This study was designed with the aim to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…1 at hospital A. CPA was detected in the skin samples of oncology personnel at two hospitals within the range of 83.1 to 144.35 ng/wipe. The result of the statistical analysis of the correlation between skin samples obtained from the author's previous study (34) and the urine samples taken from the same personnel in this study were significant (P = 0.002, R = 0.67). Based on an observational field study in our hospitals, the majority of the personnel do not follow the guidelines and procedures recommended by international institutions and do not use the recommended safety equipment.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…1 at hospital A. CPA was detected in the skin samples of oncology personnel at two hospitals within the range of 83.1 to 144.35 ng/wipe. The result of the statistical analysis of the correlation between skin samples obtained from the author's previous study (34) and the urine samples taken from the same personnel in this study were significant (P = 0.002, R = 0.67). Based on an observational field study in our hospitals, the majority of the personnel do not follow the guidelines and procedures recommended by international institutions and do not use the recommended safety equipment.…”
Section: Discussionmentioning
confidence: 50%
“…Occupational exposure to CPA drug was reported to be taking place through respiratory and skin routes (35)(36)(37). The authors of this study have recently published articles measuring the external exposure of the same oncology personnel's exposure to CPA through the skin route (34,38). In accordance with our previous data for the external occupational exposure to CPA through skin contamination, and also with the data from the urinary concentration of the same group of personnel in the present study, significant statistical correlation was observed (P < 0.05).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Readers interested in more information on computing topological indices of the link of graphs can be referred to Refs. [18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%